EVALUASI DETERMINAN KEMATIAN PASIEN UNIT INTENSIF ANAK: STUDI RETROSPEKTIF RUMAH SAKIT TERSIER INDONESIA TIMUR - Sukmapermata, Bunga; Hartawan, I Nyoman Budi; Suparyatha, Ida Bagus Gede; Kanya Wati, Dyah (Journal of Health Service Management, 2025)
Background: Understanding the characteristics of pediatric mortality is essential for improving and evaluating the quality of care in Pediatric Intensice Care Unit (PICU). Such insights allow for more effective prioritization and allocation of limited resources, Objective: To identify the determinant factors contributing to mortality in PICU. Methods: This study was a descriptive study using medical record data from a tertiary referral hospital in Denpasar, Bali. Results: A total of 51 patients who died in the Pediatric Intensive Care Unit (PICU) were included. The median age of deceased patients was 3.33 years (IQR 0.5–9.92), with a higher proportion of female patients and those suffering from malnutrition. Most of the deceased patients were categorized as priority level 4 for PICU care. The most common diagnosis at admission was pneumonia, and the most patients were referred from other inpatient wards within the same hospital. A total of 35 cases progressed to sepsis, with a median procalcitonin level of 5.19 ng/mL (IQR 0.98–19.77), and sepsis accounted for 64.7% of the deaths in the PICU. The PELOD-2 score, calculated without lactate, had a median value of 6 (IQR 4–9), which may represent a threshold for mortality risk in our PICU. The mortality rate in our PICU during the study period was 22.27%. Conclusion: Infection remains the primary cause of death among pediatric patients in the PICU, particularly in those with severe comorbidities commonly referred to tertiary care centers. These findings emphasize the need to strengthen infection control measures in general wards and optimize fluid management within the PICU. Given the frequent mismatch between demand and capacity, stricter patient admission criteria are essential to ensure that intensive care resources are allocated to those with the highest clinical need and greatest potential for benefit.